Psychopharmacology : 501 questions to help you pass the boards - Selvaraj, Vithyalakshmi , 1977-; Ramaswamy, Srira , 1972- (Wolters Kluwer/Lippincott Williams & Wilkins Heath, 2012)
"Focusing on the area that many psychiatrists regard as the most complex and challenging to master for the Boards, this book offers extensive practice questions with thoughtful rationales, covering all drug groups and offering clinical vignettes similar to those on ABPN exam"--Provided by publisher.